Association of baseline and change in global longitudinal strain by computed tomography with post-transcatheter aortic valve replacement outcomes. (13th November 2021) - Fukui, Miho; Hashimoto, Go; Lopes, Bernardo B C; Stanberry, Larissa I; Garcia, Santiago; Gössl, Mario; Enriquez-Sarano, Maurice; Bapat, Vinayak N; Sorajja, Paul; Lesser, John R; Cavalcante, João L
Abstract: Aims: Transcatheter aortic valve replacement (TAVR) procedural planning requires computed tomography angiography (CTA) which allows for the assessment of left ventricular global longitudinal strain (CTA-LVGLS). There is, however, limited data on the feasibility of CTA-LVGLS, and its prognostic value. This study sought to evaluate the incremental prognostic value of baseline CTA-LVGLS, change in CTA-LVGLS after TAVR, and their association with post-TAVR outcomes. Methods and results: A total of 431 patients who underwent multiphasic gated CTA using dual-source system for TAVR planning at baseline and 1-month follow-up were included [median (interquartile range) age, 83 (77–87) years; 44% female, STS-PROM score: 3.3 (2.3–5.1)%, Echo-left ventricular ejection fraction (LVEF): 60 (55–65)%, CTA-LVGLS: −18.0 (−21.6 to −14.2)%, feasible in 97% of patients]. CTA-LVGLS was measured using dedicated feature-tracking software. Over a median follow-up of 19 (13–27) months, 99 endpoints of all-cause death or heart failure hospitalization occurred. The relative hazard of the endpoint increased as baseline CTA-LVGLS worsened with −18.2% as the threshold for higher events ( P  = 0.005). After adjustment for baseline characteristics, CTA-LVGLS remained associated with the endpoint [hazard ratio (HR) (95% confidence interval, CI), 1.08 (1.03–1.14); P  = 0.005] and incrementally improved prognostication (C-index difference, 0.026). Although CTA-LVGLS improved after TAVR [−18.3 (−21.6 to −14.3)% vs. −18.7 (−21.9 to −15.4)%, P  < 0.001], patients without CTA-LVGLS improvement had higher risk of the endpoint than those with improvement or preserved baseline global longitudinal strain [HR (95% CI), 1.92 (1.19–3.12); P  = 0.008]. Conclusions: In this predominantly low-risk TAVR cohort of patients, mostly with normal LVEF, assessment of CTA-LVGLS is highly feasible improving risk stratification by providing independent and incremental prognostic value over clinical and echocardiographic characteristics. Graphical Abstract: